Relationship between Parenting Style and Maternal Personal Hygiene with Children’s Personal Hygiene in North Jakarta - Rebeka Milenia Magany; Prissilia Nanny Djaya; Felicia Kurniawan (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Personal hygiene habits need to be practiced since early childhood because they are essential mechanisms in breaking the chain of transmission of various diseases. Important factors that affect children's personal hygiene are parenting style and maternal personal hygiene. This study aimed to determine the relationship between parenting style and maternal personal hygiene with their children’s personal hygiene.Methods: This study was an analytic observational study with a cross-sectional method conducted in July-December 2019. Parenting style and personal hygiene questionnaires were completed by students’ mothers from four primary schools in North Jakarta (n 327). The study used the total sampling method Data collection was analyzed using Chi-square and Fisher exact test.Results: The study showed that 98.5% of students were raised with a non-exposure or authoritative parenting style, of which 57.5% of mothers had poor personal hygiene., Due to this, 61.8% of students had poor personal hygiene. Interestingly, there was a significant relationship between maternal personal hygiene and children's personal hygiene (p = 0.023). However, there was no significant relation between parenting style and children's personal hygiene (p = 0.065).Conclusions: There is no significant relationship between parenting style and children's personal hygiene. There is a significant relationship between maternal personal hygiene and children's personal hygiene. Therefore, parents need to apply the proper parenting style supported by other factors, such as good maternal personal hygiene, to encourage and educate children in achieving good personal hygiene.